Pendaftaran Kebaya Sebagai Warisan Tak Benda Ke UNESCO: Analisis Framing Zhongdang Pan dan Gerald M Kosicki Dalam Media Kompas.com dan Berita Satu.com - Dellya Putri Apriliany; Hendra Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
In order to analyze news and the media, this study looks into the field of journalism. As a result, the purpose of this study was to determine how each media presented an event. The information gathered in this study is analyzed and described using a quantitative descriptive method. Additionally, the news article "Kebaya Registration Debate as Intangible Heritage to UNESCO" served as the research object, and the news websites Kompas.com and Beritasatu.com served as the subjects of this study. Then, this study uses Zhongdang Pan and Gerald M. Koscki's framing theory to collect and analyze data using their framing research scheme, which includes four components: syntax, script, thematic, and rhetoric. The findings of the research can be used as a reference to help readers learn more about Zhongdan Pan and Gerald M. Kosicki's theory of framing analysis and the differences in framing used by different media outlets to report on a research event.